2017
DOI: 10.3389/fnins.2017.00407
|View full text |Cite
|
Sign up to set email alerts
|

Triarchic Psychopathy Dimensions in Chimpanzees (Pan troglodytes): Investigating Associations with Genetic Variation in the Vasopressin Receptor 1A Gene

Abstract: Vasopressin is a neuropeptide known to be associated with the development and evolution of complex socio-emotional behaviors including those relevant to psychopathic personality. In both humans and chimpanzees, recent research suggests a strong genetic contribution to individual variation in psychopathic traits. To date, however, little is known concerning specific genes that might explain the observed heritability of psychopathy. In a relatively large sample of captive chimpanzees (N = 164), the current study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Within this framework, recent investigation of these dispositional dimensions of psychopathy has been extended to our closest living relatives, chimpanzees (Latzman et al, 2016a(Latzman et al, , 2017a(Latzman et al, , 2017b, providing a basis for comparative research on their behavioral and neurobiological aspects. Specifically, extending the human literature on the triarchic model, Latzman and colleagues (2016a) developed a chimpanzee operationalization of psychopathic personality organized around the triarchic conceptualization.…”
Section: Elucidating Foundations Of Personality Pathology Though Chimmentioning
confidence: 99%
“…Within this framework, recent investigation of these dispositional dimensions of psychopathy has been extended to our closest living relatives, chimpanzees (Latzman et al, 2016a(Latzman et al, , 2017a(Latzman et al, , 2017b, providing a basis for comparative research on their behavioral and neurobiological aspects. Specifically, extending the human literature on the triarchic model, Latzman and colleagues (2016a) developed a chimpanzee operationalization of psychopathic personality organized around the triarchic conceptualization.…”
Section: Elucidating Foundations Of Personality Pathology Though Chimmentioning
confidence: 99%
“…In rhesus macaques, variation in sociability is associated with measures of vasopressin in cerebral spinal fluid, despite no significant associations between AVPR1A alleles and social behaviors, such as grooming, passive contact, approaches and aggression . In chimpanzees, several studies have shown that polymorphisms in AVPR1A are associated with individual variation in different dimensions of personality, including social “smarts” (using coalitions and engaging in reciprocal grooming and play) and sociability . Additional studies have shown that chimpanzee AVPR1A polymorphisms are associated with responses to sociocommunicative cues, videos and sounds of unfamiliar individuals and mirror self‐recognition .…”
Section: Introductionmentioning
confidence: 99%